PERANAN KURATOR DALAM PROSES PENYELESAIAN BOEDEL PAILIT KEPADA MASING-MASING KREDITOR - Oki Amrita Wijaya, Ida Ayu; Putra Ariana, I Gde (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 05, Juli 2014, 2014)
This paper shall be entitled as “Role of Curator in Bundling Default to Creditors”. It shall apply normative legal research combined with statutory approach. Default or statement of bankcruptcy shall resulted towards debtor in capability in managing its asset. Within such circumstances, authority shall be undertaken by curator in setting the bankcruptcy. Thus, the authority shall start from management and settlement.
Keywords: Bankcruptcy, Management, Settlement